The Importance of the Regional Arbitration Commission in the System of Liability for Breach of Public Finance Discipline - Sołtyk, Piotr (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2018)
The article examines the activities of the regional arbitration commission (RAC) in the system of liability for breach of public finance discipline. It covers attributed acts of violations of public finance discipline, applications for punishment, derogations from punishment, verdicts of acquittal and verdicts of punishment of the accused.The aim of the article is to present selected issues of RAC activities over the years 2011–2016. To this end, the subject literature, legal regulations and reports of the Main Arbitration Commission in cases of violation of public finance discipline are analysed.